2022
DOI: 10.1175/jpo-d-22-0009.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of eddying abyssal mixing layers over sloping rough topography

Abstract: The abyssal overturning circulation is thought to be primarily driven by small-scale turbulent mixing. Diagnosed watermass transformations are dominated by rough topography “hotspots”, where the bottom-enhancement of mixing causes the diffusive buoyancy flux to diverge, driving widespread downwelling in the interior—only to be overwhelmed by an even stronger up-welling in a thin Bottom Boundary Layer (BBL). These watermass transformations are significantly underestimated by one-dimensional (1D) sloping boundar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…This is consistent with one-dimensional idealized boundary layer solutions for sloping bathymetry with parameters similar to ours, which suggest that diapycnal upwelling occurs in a layer of height O(50 m) (Holmes & McDougall, 2020). Similarly, the quasi-realistic Brazil Basin simulations of Drake et al (2022) with 6 m vertical resolution demonstrated marginally resolved diapycnal upwelling in a bottom boundary layer of O(10) m.…”
Section: Simulated Water Mass Transformationsupporting
confidence: 89%
See 4 more Smart Citations
“…This is consistent with one-dimensional idealized boundary layer solutions for sloping bathymetry with parameters similar to ours, which suggest that diapycnal upwelling occurs in a layer of height O(50 m) (Holmes & McDougall, 2020). Similarly, the quasi-realistic Brazil Basin simulations of Drake et al (2022) with 6 m vertical resolution demonstrated marginally resolved diapycnal upwelling in a bottom boundary layer of O(10) m.…”
Section: Simulated Water Mass Transformationsupporting
confidence: 89%
“…Similarly, the quasi‐realistic Brazil Basin simulations of Drake et al. (2022) with 6 m vertical resolution demonstrated marginally resolved diapycnal upwelling in a bottom boundary layer of O (10) m.…”
Section: Water Mass Transformationmentioning
confidence: 67%
See 3 more Smart Citations